In vitro and in vivo evaluation of Ulva lactuca for wound healing - Chien-Hsing Wang; Zih-Ting Huang; Kuo-Feng Tai (PLoS ONE, 2025)
Ulva lactuca (U. lactuca) is an important seaweed species. Some ingredients in this species are thought to accelerate wound healing. However, limited data on the use of seaweed for wound healing exists. This study examined whether ethanol or aqueous extracts of U. lactuca promote antioxidant and anti-inflammatory properties in vitro and wound healing in vitro and in vivo. Cell proliferation, antioxidation, and migration were observed in NIH3T3 cells treated with U. lactuca extract in vitro. Both U. lactuca extracts were examined for their ability to inhibit inflammatory cytokine synthesis in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. In vivo experiments involved four groups of albino mice (BALB/c; 10 mice per group). One 1.0 cm2 wound was created via excision of full-thickness skin on the back of all mice. Group I mice were treated topically with the ethanol extract of U. lactuca (25 mg/mL) for 10 d. Group II mice were treated topically with an aqueous extract of U. lactuca (12.5 mg/mL) for 10 d. Group III mice received topical application of phosphate-buffered saline solution. Group IV mice wounds were maintained without treatment. Both extracts considerably increased fibroblast proliferation. The antioxidant activity of the U. lactuca extract was determined using a total antioxidant capacity assay. Both extracts inhibited the release of tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) from LPS-mediated inflammation in RAW 264.7 cells. These extracts also upregulated the expression of Th2 cytokines such as transforming growth factor beta 1 (TGF-β1) and interleukin 10 (IL-10) in RAW 264.7 cells under pro-inflammatory conditions. Both extracts enhanced the migratory ability of NIH3T3 cells. U. lactuca ethanol extract enhances wound healing properties in vivo. These results suggest that bioactive compounds derived from U. lactuca extract are beneficial for wound healing and anti-inflammatory therapies.